Association between Cysticercosis and Neoplasia: A Study Based on Autopsy Findings - Camila Lourencini Cavellani; Aline Cristina Souza da Silva; Grace Kelly Naves de Aquino Ribeiro; Lívia Ferreira Oliveira; Mara Lúcia Fonseca Ferraz; Vicente de Paula Antunes Teixeira (The Scientific World Journal)
Chronic infections including the cysticercosis induce inflammatory cells to produce free radicals and synthesize carcinogenic toxins. The cells with genetic mutations proliferate in a disorganized manner, leading to the development of neoplasia. The aim of the present study was to demonstrate the relation between cysticercosis and neoplasia. Patients autopsied were divided into 4 groups: patients with neoplasia and cysticercosis (NC), patients with neoplasia only (NN), patients with cysticercosis only (CC), and patients without neoplasia or cysticercosis (WW). Of 2012 autopsy reports analyzed, 0.4 showed NC. In groups CC and NC, the most common location of the parasite was the brain. There was a predominance of three or more cysticerci in groups NC and CC. In the NC group, all had malignant neoplasms, and was predominance of benign neoplasm in NN group. The digestive system was the most frequent neoplasia. By calculating odds ratio, rate of neoplasia in patients with cysticercosis was 0.74. In conclusion, the demographic profile of patients with cysticercosis and neoplasia is similar to that of patients with cysticercosis alone. The incidence of cysticercosis and neoplasia was greater in older patients suggesting that immunosenescence may contribute to development of neoplasia promoted by cysticercosis.